2011
DOI: 10.1108/17570971111197175
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existing mental health and substance use and alcohol difficulties – why do we persist with the term “dual diagnosis” within mental health services?

Abstract: Purpose -The term ''dual diagnosis'' has been widely accepted as referring to co-existing mental illness and substance misuse. However, it is clear from the literature that individuals with these co-existing difficulties continue to be excluded from mainstream mental health services. The term ''dual diagnosis'' can be pejorative and therefore, complicate or obstruct engagement. It is argued within this paper that the association between mental illness and substance misuse (including alcohol misuse) is an intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
(73 reference statements)
0
22
0
2
Order By: Relevance
“…more or less directive) and provision of their current situation. These principles are similar to those put forward by Guest and Holland (2011) for supporting individuals with complex presentations, reflecting best practice and expert advice in comorbidity treatment planning and delivery.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…more or less directive) and provision of their current situation. These principles are similar to those put forward by Guest and Holland (2011) for supporting individuals with complex presentations, reflecting best practice and expert advice in comorbidity treatment planning and delivery.…”
mentioning
confidence: 85%
“…The co-existence of mental and substance use disorders (dual diagnosis) occurs in approximately 25-50 percent of substance users (Teesson et al, 2012), and is even higher when sub-threshold mental health symptoms are considered (Guest and Holland, 2011). Despite growing recognition and a rapidly increasing international evidence base for effective treatments, a serious level of unmet need for treatment exists for people experiencing dual diagnosis.…”
mentioning
confidence: 99%
“…In addition to BFHJ, all offenders accessing Gateways are also provided with a peer mentor to meet them at the prison gate, and support to secure accommodation back in the community, in addition to help with finances, employment etc two areas of difficulties and contribute to the literature around the nature of 'dual diagnosis' (Guest & Holland, 2011;Hamilton, 2014). Rather than focussing purely on the substance misuse and mental health difficulties of prisoners, this study also attempted to make sense of these difficulties through understanding their relations to the experiences and events that have occurred in their lives, the other multiple and complex needs substance-involved prisoners might have (Rosengard et al, 2007), and how these issues may have impacted on their ability to terminate their substance misuse in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of substance misuse and mental health difficulties is often referred to as 'dual diagnosis', although, some have suggested that as a concept, dual diagnosis may not capture the full range of multiple and complex difficulties such individuals may experience (Guest & Holland, 2011) and therefore the range of needs that should be recognised and addressed in interventions for dually diagnosed individuals (McSweeney & Hough, 2006;Rutherford & Duggan, 2009). Such multiple and complex needs may include coming from a background of high social and economic deprivation, having been removed from biological parents and becoming a 'looked after child' within the care system, and having experienced periods of homelessness (Rosengard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation